Revista Habanera de Ciencias Médicas: A vision from scienciometry - Valdés Balbín, Ray (2017)
Introduction: Teamwork among editors, director, and the Editorial Board is essential in order to guarantee a satisfactory editorial process. The main purpose of this association is to publish papers with an adequate scientific-methodological rigor, which demands a great effort in order to maintain quality, guarantee scientific validity, and protect potential readers who have access to the final product. Objective: To characterize the Revista Habanera de Ciencias Médicas from metric indicators. Material and methods: A scientific and metric study of this bibliographic variables published by Publish or Perish, and metric indicators provided by SciELO and SciELO Citation Index. Results: The journal has an h-index of 18, with more than a thousand published authors. The average number of authors per article is 3 and there is a favorable balance between the distribution of cited and non-cited articles. It makes more citations than the ones it receives, and it does not have a high number of self-cites. Conclusions: The Revista Habanera de C iencias Médicas has shown results that place it among the best positioned journals with health related issues in greater coverage databases, which is demonstrated from the analysis of its metric indicators.